Overview Strategic Masterplan to Mitigation Climate Change on Tourism Industry: A Systematic Literature Review - Puspitasari, Dyah Ayu Kunthi; Taali, Muhammad; Farani, Dinesh Basti; Mudofir, Imam; Amri, Lala Hucadinota Ainul (IJOSMAS, 2024)
Currently, climate change is a major focus in various industrial sectors, including tourism. Significant climate change has caused changes in tourist behavior, from changes in visiting times to choosing tourist destinations. If the tourism industry does not consider the impacts of climate change, this can affect marketing strategies and regional development, especially when climate change occurs. The Integrated Tourism Master Plan (ITMP), prepared by the World Bank in 2018, provides recommendations on various aspects of tourism development, including mitigating the impacts of climate change. This study uses a qualitative method with a Systematic Literature Review approach. The sample used is a masterplan document from the local government. The results of the study show that although the ITMP issued by the World Bank contains guidelines for climate change mitigation in the tourism sector, the guidelines have not been fully implemented or adapted in the regional master plan. However, the regional masterplan document has shown attention to climate change. Improvement and implementation of the master plan for climate change mitigation are needed. The recommendations given are to adopt aspects of tourism development related to climate change prevention and to prepare relevant implementing regulations.